1994
DOI: 10.1099/0022-1317-75-7-1785
|View full text |Cite
|
Sign up to set email alerts
|

The complete sequence of a human astrovirus

Abstract: We have determined the complete genomic sequence of human astrovirus serotype 1 isolated in Newcastle upon Tyne. The genome is 6813 nucleotides long and contains three sequential open reading frames (ORFs). The two closest to the 5' end are linked by a ribosomal frameshifting motif and contain sequence motifs indicative of non-structural virus proteins: serine protease and RNA-dependent RNA polymerase. A nuclear addressing sequence is also located here. The 3' ORF encodes the virion structural polypeptides as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
100
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(101 citation statements)
references
References 23 publications
0
100
0
1
Order By: Relevance
“…It was, therefore, of great help that we initially obtained two sequences located about 2 kb apart, facilitating the rapid amplification and sequence determination of the 39 two-thirds of the genome. The presence of poly(A) tails in all 39 most sequence parts indicated that the genome is polyadenylated, as is the case for all other astroviruses for which full-length sequences have been determined to date (Imada et al, 2000;Jiang et al, 1993;Koci et al, 2000;Lewis et al, 1994;Mendez-Toss et al, 2000;Oh & Schreier, 2001;Willcocks et al, 1994). The 59 most extreme sequence proved to be more difficult to obtain.…”
Section: Discussionmentioning
confidence: 99%
“…It was, therefore, of great help that we initially obtained two sequences located about 2 kb apart, facilitating the rapid amplification and sequence determination of the 39 two-thirds of the genome. The presence of poly(A) tails in all 39 most sequence parts indicated that the genome is polyadenylated, as is the case for all other astroviruses for which full-length sequences have been determined to date (Imada et al, 2000;Jiang et al, 1993;Koci et al, 2000;Lewis et al, 1994;Mendez-Toss et al, 2000;Oh & Schreier, 2001;Willcocks et al, 1994). The 59 most extreme sequence proved to be more difficult to obtain.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to humans, members of this virus family infect a variety of other young mammals and birds, causing diseases ranging from diarrhea to nephritis (18). Astroviruses are small, nonenveloped, icosahedral particles with a single-stranded mRNA genome (ϳ7 kb) that is organized into three open reading frames (ORFs); ORFs 1a and 1b encode nonstructural proteins (11,16,34), whereas ORF2 encodes the coat protein (CP) precursor (16,32). CP precursors assemble into particles, encapsidating the viral genome, and are subsequently cleaved extracellularly by trypsin, which renders the virion infectious (1,20).…”
mentioning
confidence: 99%
“…[89][90][91][92] Human AstVs are among the leading causative agents of viral gastroenteritis in young children. 93 Although AstV particles have been found in intestinal epithelial cells of children with diarrhea, indicating shedding through feces, the pathology and immunity to AstV infection remains unclear.…”
Section: Astrovirusmentioning
confidence: 99%